Basics of navigation implant prosthetics planning - Miličić-Lazić Minja; Prokić-Marić Aleksandra; Todorović Ana; Lazić Vojkan (Serbian Medical Society - Dental Section, Belgrade, 2020)
Due to the development of digital technologies, the modern concept of prosthetic-guided implantology is based on non-invasive surgical and restorative techniques. Computer-aided planning, computer-guided workup and computer-guided surgery have largely ensured the predictability of the therapeutic outcome. This is supported by research data related to the frequency of implant therapy, according to which in the first half of 2020 there was an increase of 9.7%. However, anatomical limitations remain a challenge for the implant team. The most common problem related to implant therapy in edentulous patients is limited edentulous space in one or more spatial planes. Improving the design of surgical guides facilitates implantation in spatially limited and complex cases. By introducing interactive computed tomography into the field of implantology, a three-dimensional approach to every aspect of planning and implantation has become possible.